A retrospective review of Cochlear implants at Chris Hani Baragwanath Hospital since 2006 - van Aardt, Michael Gustaf (My University, 2022)
Objectives: To conduct an audit of all cochlear implant recipients in a South African public hospital, describing hearing loss etiology and audiometric profiles between age categories. This was contrasted to local implant candidacy criteria and compared to international criteria. Methods: Retrospective review Results: Of the 117 implanted recipients included, the majority were female and of African ethnicity. The predominant cause of deafness was ototoxicity related to the treatment of tuberculosis (32% of all recipients). The prevalence of human immunodeficiency virus in the sample was 34%, mostly adults (92.5%). Pre-operative unaided audiometric thresholds appear to be similar between all subgroups, but aided thresholds are significantly better in patients with tuberculosis related deafness. Human immunodeficiency virus appears to not affect hearing thresholds on regression analysis. All patients performed uniformly poorly on aided speech discrimination scoring. Conclusion: The etiology for hearing loss for implant recipients at our institution are different to those in international studies with idiopathic hearing loss accounting for far fewer cases. Based on the current funding model, the indications for implantations at our institution are limited to profound bilateral hearing loss, despite having more lenient criteria for implant candidacy.
A research report submitted in fulfilment of the requirements for the degree of Master of Medicine in Otorhinolaryngology to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2022